Menthyl esterification allows chiral resolution for the synthesis of artificial glutamate analogs - Morokuma, Kenji; Tsukamoto, Shuntaro; Mori, Kyosuke; Miyako, Kei; Sakai, Ryuichi; Irie, Raku; Oikawa, Masato (Beilstein Journal of Organic Chemistry, 2021)
Herein, we report the enantiospecific synthesis of two artificial glutamate analogs designed based on IKM-159, an antagonist selective to the AMPA-type ionotropic glutamate receptor. The synthesis features the chiral resolution of the carboxylic acid intermediate by the esterification with ʟ-menthol, followed by a configurational analysis by NMR, conformational calculation, and X-ray crystallography. A mice in vivo assay showed that (2R)-MC-27, with a six-membered oxacycle, is neuroactive, whereas the (2S)-counterpart is inactive. It was also found that TKM-38, with an eight-membered azacycle, is neuronally inactive, showing that the activity is controlled by the ring C.
Keywords: chiral resolution; configurational analysis; glutamate; metathesis; neuroactivity